고압 다이캐스팅으로 제조된 Al-10Si-0.3Mg-0.6Mn 합금에서 blister 발생과 강도의 균형을 고려한 최적 열처리 공정 설계 - 김수배; Soo-bae Kim; 조영희; Young-hee Cho; 조민수; Min-su Jo; 이정무; Jung-moo Lee (한국주조공학회지, 2020)
The aim of this study was to optimize a solid solution treatment for a high pressure die casting Al-10Si-0.3Mg-0.6Mn alloy to avoid blistering and to improve the strength of the alloy. To achieve this goal, the number density of the blisters and the strength of the alloy under various solid solution treatment (SST) conditions were evaluated. The SST was performed at 470, 490, 510 and 530℃ for 20, 60, 120, 240 and 480 min on the alloy. The number density of the blisters increased with the increasing temperature and time of the SST and the defect area fraction. The yield strength of the alloy after the T6 heat treatment increased with the increasing SST temperature and time. Based on the results, it is suggested that SST should be performed at 510℃ within 60 min. or at 470 and 490℃ within 240 min. to avoid blistering and to improve the strength.